Respirable particulate (PM10) and its heavy metals concentrations from bauxite mining in the vicinity of urban Kuantan, Malaysia: inhalation health risk assessment - Sajali, Intan Nor Lyana; Hashim, Zailina; Hashim, Jamal Hisham (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Bauxite ore contain various heavy metals especially aluminum, if exposed excessively is detrimental to the respiratory system. Objective: This study aimed at determining the PM10 and its Al, As, Cd, Cr, Ni and Pb content and assessing the inhalation health risk assessment (HRA) among the community. Method: This cross-sectional study was conducted in Kuantan on 162 randomly selected respondents in three residential areas; Felda Bukit Goh (FBG), Jalan Besar Bukit Goh (JBBG) and Kuantan Port Consortium Flat (KPCF). Questionnaires were used to obtain the background information and health symptoms. PM10 with its heavy metals were subsampled for 24 hours using air sampling pumps in 42 randomly sub-sampled households from the 3 areas. Results: PM10 exceeded 150 µg/m3 and the Al, Cd, As, Cr, Ni and Pb levels exceeded the standard limit. The hazard quotient (HQ) of Cd in JBBG (4.13), Cr in FBG (74.06), JBBG (84.41), KPCF (76.87) and Ni in FBG (60.53), JBBG (66.95) and KPCF (58.81) exceeded the HQ value of 1. The lifetime cancer risk (LCR) exceeded the level of 0.0000001 for Cr in FBG (0.0252), JBBG (0.0288) and KPCF (0.0262), as well as for Ni in the FBG (0.000184), JBBG (0.000204), and KPCF (0.000179) areas. Conclusion: The PM10 levels exceeded the USEPA guidelines while Al, Cd, As, Cr, Ni and Pb exceeded the ATSDR limit. The Cd, Cr and Ni posed non-carcinogenic and carcinogenic health risks. Therefore, health risks from the PM10, Cd, Cr and Ni exposures were found in this study.